A Handbook on Housekeeping and Disinfection Practices for Healthcare Facilities - Gupta, S. K. Shakti Kumar (Jaypee Brothers Medical Publishers, 2021)
This book is a comprehensive compendium on housekeeping and disinfection practices, and biomedical waste management. This book consists of 13 chapters, which include housekeeping services, staffing, training, cleaning in healthcare organizations, pest management, quality and hospital housekeeping, outsourcing of housekeeping services, sewage treatment plant, Kaya Kalp scheme, and housekeeping services in hospitals in COVID-19 environment. Each chapter highlights a specific issue centered on managing housekeeping services and disinfection practices in a hospital environment. This book outlines the training programs needed to inculcate and update the cleaning, disinfection, and biomedical waste management skills of the staff. This book will help the hospital planners, policy makers, medical administrators, nursing administrators, sanitation officers, management students, human resource managers, and other key professionals to understand how to operate and manage housekeeping in a hospital.